The Armed Forces of China - Ji, You 1955- (London I.B. Tauris Publishers, 1999)
This analysis of China's military resources and the impact of new programmed of investment in technology and manpower management foresees the nature and shape of China's current strength, and its likely future capabilities.
Includes Illustration, Maps, Notes, Bibliography and Index.
Keywords: Military Policy -- China -- Armed Forces